PENGARUH TIME BUDGET PRESSURE, LOCUS OF CONTROL, INDEPENDENSI AUDITOR, KOMITMEN PROFESIONAL TERHADAP PERILAKU PENURUNAN KUALITAS AUDIT - Nabilasari, Desfrita; Suyono, Eko; Pratiwi, Umi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This study aims to determine the effect of time budget pressure, locus of control, auditor independence, and professional commitment on reduced audit quality behaviour. The population in this study are auditors who work at the public accounting firm in South Jakarta. The sampling technique uses convenience sampling. The final sample obtained was 100 auditors. Data collection method is done through a questionnaire using data analysis in the form of Multiple Regression Analysis on the SPSS . The result of this study indicate that: (1) Time Budget Pressure has a positive effect on Reduced Audit Quality Behaviour; (2) external locus of control has a positive effect on Reduced Audit Quality Behaviour; (3) Auditor Independence does not have a negative effect on Reduced Audit Quality Behaviour; (4) Professional Commitment does not have a negative effect on Reduced Audit Quality Behaviour.